C3 and C4 complement components in autoimmune hepatitis. - AL-Obeidy, Eman Sh.; Mousawy, Khalida M.; AL-Rawi, Faruk (Journal of the Faculty of Medicine Baghdad, 2007)
Background: . Autoimmune hepatitis (AIH) is an unresolving inflammation of the liver of unknown cause associated with interface hepatitis on histological examination,hypergammaglobulinemia and presence of circulating autoantibodies. Antibody-mediated tissue injury might be responsible for tissue injury in AIH therefore; a number of studies have been focused on the complement system in these patients . The aim of the study is to estimate the level of complement (C3 and C4) in different types of Autoimmune hepatitis (AIH). Methods: The study M’as performed on 73 Iraqi patients with autoimmune hepatitis (AIH), attending the teaching hospital for gastroenterology and liver disease in a period betM’een November 2003 and July 2004. : Anti- soluble liver ANA , SAM,LKA1-1 ,and LC-1 Abs were detected using Enzyme-Linked Immunosorbent Assay (ELISA) technique . Anti-SLA/LP was detected using the Euroline method. Quantitation of serum C3 and C4 of the study groups were carried by single radial immudiffusion (SRID) test. Equal volume Results: Significant differences M’as observed between AIH patients and healthy control group in the mean level of C3 and C4. In addition, level of C4 in the sera of patients with type 2 was lower than those of type 1 and 3. Conclusion:It M’as conclude that patients with MH do not have abnormal catabolism of complement or increased level of cleavage products of C3, whereas, the depression of complement level may reflect decreased hepatic synthesis.